Hair Tonic Formulation of Green Spinach Leaf Extract (Amaranthus viridis L.) as a Hair Growth Agent for New Zealand Rabbits (Oryctolagus cuniculus) - Shinta Putri Rahmawati; Septian Maulid Wicahyo; Annie Rahmatillah (International Journal of Health Engineering and Technology, 2026)
Hair loss can lead to baldness, and many commercial hair tonics contain synthetic chemicals with potential side effects. This study explores the use of natural ingredients, specifically green spinach leaf (Amaranthus viridis) extract, as an alternative. Green spinach leaves are rich in flavonoids, tannins, saponins, and antioxidants, which are known to stimulate hair growth. The research aims to evaluate the hair growth activity of green spinach leaf extract on New Zealand rabbits (Oryctolagus cuniculus), assess the physical quality of hair tonic formulations at three concentrations (5%, 10%, 15%), and determine the most effective formula. The study used a quantitative, descriptive, and experimental approach. Extracts were obtained via maceration with 96% ethanol and formulated into hair tonics. Rabbits were divided into six groups: untreated, positive control, negative control, and three treatment groups (F1, F2, F3). Phytochemical screening confirmed the presence of flavonoids, saponins, and tannins. Physical stability tests showed all formulations were stable. Statistical analysis (One-Way ANOVA and Post Hoc Tukey) revealed significant differences in hair growth between treatment and negative control groups, with the 15% formula (F3) yielding the highest average hair growth (10.67 mm).